Interesting Beings and Racial Difference in Fictions of the Haitian Revolution - Michael Boyden (Karib)
This article examines two novels about the Haitian Revolution, namely Leonora Sansay’s epistolary novel Secret History, or the Horrors of St. Domingo (1808) and an extended rewriting of this novel entitled Zelica, the Creole (1820), which has been attributed to Sansay. While Secret History narrates the events in Haiti through the lens of the American coquette Clara and her prudish sister Mary, Zelica transforms that sororal relationship into a crossracial friendship between Clara and the mixed-race character Zelica. In Secret History, Clara escapes both Saint Domingue and her abusive husband. In Zelica, she is killed by Zelica’s father, a philanthropist who believes in emancipation through amalgamation. The aim of the article is not to provide definitive answers to the question of Zelica’s authorship but to examine the motivational claims underlying the rewriting. It argues that the foregrounding of a mixed-race character reflects the increasing fixation on race-mixing in nineteenth century culture. The death of Clara at the hands of the philanthropist De La Riviere is read as an implicit creole critique of gradual abolitionism.